Switching intermolecular interactions by confinement in carbon nanotubes. Issue 4 (21st November 2014) - Chamberlain, T. W.; Lebedeva, M. A.; Abuajwa, W.; Suyetin, M.; Lewis, W.; Bichoutskaia, E.; Schröder, M.; Khlobystov, A. N.
Abstract : Carbon nanotube encapsulation offers a mechanism to trap kinetically rather than thermodynamically favoured supramolecular arrays. Abstract : The encapsulation of trityl-functionalised C60 molecules inside carbon nanotubes drastically affects the intermolecular interactions for this species. Whilst the orientations of molecules in the crystal are often controlled by thermodynamics, the molecular orientations in nanotubes are a result of kinetic control imposed by the mechanism of entry into and encapsulation within the nanotube.